Heat transfer and fluid flow in minichannels and microchannels edited by Satish G. Kandlikar ... [et al.]. - Kandlikar, S. G. (Satish G.) (Elsevier, 2005)
Presenting its findings in a manner that will be of interest to both designers and researchers, this text is a sourcebook for thos involved in the design processes of microchannel flow passages in a heat exchanger.